Investigating Gender Disparities in Electronics Engineering Program Enrollments at a State University in the Philippines - Beltran, Joshua Kyle D.; Arboleda, Edwin R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study investigates gender disparities within the electronics engineering program at a state university in the Philippines from 2020 to 2023. There is a significant gender gap occurring in this area of engineering studies that necessitates further investigation to understand gender-related enrollments. The researchers employed data analysis on enrollment data, which included year, course, and gender. By means of data manipulation and visualization using the Python programming language, it facilitated data analysis with Jupyter Notebook. The findings revealed that despite fluctuations over the specified years, male student enrollees significantly outnumbered female student enrollees in the program. Male enrollees have consistently formed around 70% to 72%, on the one hand, female enrollees covered approximately 28% to 30% over the years. The research outcomes implied that gender differences remain significant, and addressing this issue is necessary. If male dominance continues in this field, significant development will not occur. Diversifying the approach to involve more women in the program is crucial to achieving greatness and fostering advancement and development in this field of study.